2012
DOI: 10.3109/09638288.2012.709909
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid haemorrhage (SAH): long-term cognitive outcome in patients treated with surgical clipping or endovascular coiling

Abstract: Study findings indicate fewer cognitive deficits following endovascular coiling. Cognitive deficits in the clipped group may be due in part to the invasive nature of neurosurgical clipping. Further prospective research with regard to long-term cognitive and emotional outcomes is warranted. IMPLICATIONS OF REHABILITATION: • Treatment of ruptured intracranial aneurysms by either endovascualar coiling or neurosurgical clipping can result in significant long-term physical disability as well as cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 24 publications
0
12
0
4
Order By: Relevance
“…The patients provided written consent and comprehensive neuropsychological test. Both treatment groups exhibited cognitive impairments in memory, attention and speed of information processing (4). Previous clinical studies have indicated that long-term survivors of aSAH frequently exhibit hypothyroidism (5,6).…”
Section: Introductionmentioning
confidence: 96%
“…The patients provided written consent and comprehensive neuropsychological test. Both treatment groups exhibited cognitive impairments in memory, attention and speed of information processing (4). Previous clinical studies have indicated that long-term survivors of aSAH frequently exhibit hypothyroidism (5,6).…”
Section: Introductionmentioning
confidence: 96%
“…Given the study biases, there is an ongoing controversy in the literature, whether (7,25,28,34,91,105) or not (7,29,55,91,99,103) coiling is preferable over surgical clipping with regard to a favorable functional and cognitive outcome. To date, only 13 SAH studies (7,24,26,28,29,34,55,58,59,89,91,99,112) have directly compared the effects of clipping and coiling on cognitive outcome, and, from those, merely two research groups (29,55) provided information on the time course of neurobehavioral impairment after aSAH. Due to the limited number of studies available addressing this issue, no final conclusion can yet be drawn.…”
Section: █ Introductionmentioning
confidence: 99%
“…Patients may experience a broad range of deficits involving memory, learning, attention, psychomotor speed, and emotional health [3][4][5]. Short-term rodent recovery models are often used to explore post-SAH mechanisms that result in neurologic deficits [6][7][8].…”
Section: Introductionmentioning
confidence: 99%